2020
DOI: 10.1186/s40359-020-00481-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between stuttering, comorbid conditions and executive function in children: a population-based study

Abstract: Background The aim of this study was to investigate the relationship between executive function (EF), stuttering, and comorbidity by examining children who stutter (CWS) and children who do not stutter (CWNS) with and without comorbid conditions. Data from the National Health Interview Survey were used to examine behavioral manifestations of EF, such as inattention and self-regulation, in CWS and CWNS. Methods The sample included 225… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 243 publications
(276 reference statements)
3
13
0
2
Order By: Relevance
“…A study examining treatment referral patterns in bilingual and monolingual children found that parents of bilingual children were more likely to report expressive language concerns compared to speech concerns while the reverse was true for monolingual children (Stow & Dodd, 2005). The prevalence of speech disorders in the present study is consistent with previous studies reporting higher rates of speech disorders in children with comorbidity and males, and decreasing rates with age (Choo, Smith & Li, 2020).…”
Section: Prevalence Of Speech Disorderssupporting
confidence: 87%
See 1 more Smart Citation
“…A study examining treatment referral patterns in bilingual and monolingual children found that parents of bilingual children were more likely to report expressive language concerns compared to speech concerns while the reverse was true for monolingual children (Stow & Dodd, 2005). The prevalence of speech disorders in the present study is consistent with previous studies reporting higher rates of speech disorders in children with comorbidity and males, and decreasing rates with age (Choo, Smith & Li, 2020).…”
Section: Prevalence Of Speech Disorderssupporting
confidence: 87%
“…The contribution of comorbid conditions (i.e. the presence of more than one disorder) is also of interest as speech disorders, neurodevelopmental disorders and health conditions commonly co-occur (Choo, Smith & Li, 2020;Silva, Couto & Molini-Avejonas, 2013). It is also unclear if these factors are correlated with symptom severity.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of language tests in children who stutter (receptive and expressive vocabulary, mean length of utterance, syntactic complexity, homogeneity analysis) shows subtle rather than clinically significant differences from controls (Ntourou et al, 2010). Similarly subtle differences between children who do and do not stutter are reported in tests related to attention and executive function (Ofoe et al, 2018;Choo et al, 2020).…”
Section: This Version June 2021 18mentioning
confidence: 97%
“…Sometimes differences in the integration of motor control with timing systems, and/or sensory or proprioceptive input, are implied. Examples include movement initiation latency and movement duration, andChoo et al (2020);Ofoe et al (2018);Ntourou et al (2011);Max (2004);Bloodstein (1995);Rosenfield & Jerger (1984)…”
mentioning
confidence: 99%
“…Os fatores não genéticos, ou ambientais (neste caso o termo ambiental diz respeito ao ambiente do ser em formação, seja no período embrionário, fetal ou perinatal), são infecções, condições maternas (consumo de álcool ou drogas psicoativas e medicamentos, exposição a poluentes, etc.) e complicações do parto (GILBERT; HY, 2017;HABERSTROH;SCHULTE-KÖRNE, 2019;CHOO;SMITH;LI, 2020;THAKRAN et al, 2020;HALLMAN-COOPER;CABERO, 2021;LEE;CACELLA;MAGNUS et al, 2021;REMIEN;.…”
Section: Introductionunclassified